Independent Replication on Genome-Wide Association Study Signals Identifies IRF3 as a Novel Locus for Systemic Lupus Erythematosus - Zhang, Feixia; Wang, Yong-Fei; Zhang, Yan; Lin, Zhiming; Cao, Yujie; Zhang, Huoru; Liu, Zhong-Yi; Morris, David L.; Sheng, Yujun; Cui, Yong; Zhang, Xuejun; Vyse, Timothy J.; et al. (Frontiers in Genetics, 2020)
Systemic lupus erythematosus (SLE) is a genetically complex autoimmune disease. Despite significant progresses in identifying susceptibility genes for SLE, the genetic architecture of the disease is far from understood. In this study, we set to replicate a number of suggestive association signals found in genome-wide association studies (GWAS) in additional independent cohorts. Replication studies were performed on Han Chinese cohorts from Hong Kong and Anhui, involving a total of 2269 cases and 5073 controls. We identified a missense variant in IRF3 (rs7251) reaching genome-wide significance by joint analysis of GWAS and replication data (OR=0.876, P=4.40E-08). Significant correlation was observed between rs7251 and lupus nephritis (LN) by subphenotype stratification (OR=0.785，P=0.0128). IRF3 is a key molecule in type I interferon production upon nucleic acid antigen stimulations and may inhibit regulatory T cell differentiation. Further elucidation of the mechanism of this association could help us better understand the pathogenesis of SLE.